Seroprevalence rates of HPyV6, HPyV7, TSPyV, HPyV9, MWPyV and KIPyV polyomaviruses among the healthy blood donors. Issue 7 (15th December 2015) - Šroller, Vojtěch; Hamšíková, Eva; Ludvíková, Viera; Musil, Jan; Němečková, Šárka; Saláková, Martina
Abstract : Human polyomaviruses HPyV6, HPyV7, TSPyV, HPyV9, MWPyV, and KIPyV have been discovered between 2007 and 2012. TSPyV causes a rare skin disease trichodysplasia spinulosa in immunocompromised patients, the role of remaining polyomaviruses in human pathology is not clear. In this study, we assessed the occurrence of serum antibodies against above polyomaviruses in healthy blood donors. Serum samples were examined by enzyme‐linked immunoassay (ELISA), using virus‐like particles (VLPs) based on the major VP1 capsid proteins of these viruses. Overall, serum antibodies against HPyV6, HPyV7, TSPyV, HPyV9, MWPyV, and KIPyV were found in 88.2%, 65.7%, 63.2%, 31.6%, 84.4%, and 58%, respectively, of this population. The seroprevalence generally increased with age, the highest rise we observed for HPyV9 and KIPyV specific antibodies. The levels of anti‐HPyV antibodies remained stable across the age‐groups, except for TSPyV and HPyV9, where we saw change with age. ELISAs based on VLP and GST‐VP1 gave comparable seroprevalence for HPyV6 antibodies (88.2% vs.85.3%) but not for HPyV7 antibodies (65.7% vs. 77.2%), suggesting some degree of crossreactivity between HPyV6 and HPyV7 VP1 proteins. In conclusion, these results provide evidence that human polyomaviruses HPyV6, HPyV7, TSPyV, HPyV9, MwPyV, and KIPyV circulate widely in the Czech population and their seroprevalence is comparable to other countries. J. Med. Virol. 88:1254–1261, 2016 . © 2015 Wiley Periodicals, Inc.